Carboxylated cellulose nanocrystals with chiral nematic property from cotton by dicarboxylic acid hydrolysis. (15th July 2021) - Lin, Chunxiang; Chen, Beiqiu; Liu, Yushi; Chen, Yiting; Liu, Minghua; Zhu, J.Y
Highlights: Dicarboxylic acid hydrolysis for producing carboxylated CNCs from cotton linter. Chiral nematic properties of carboxylayted CNCs with carboxyl groups. Recyclability of dicarboxylic acids and recycling on CNC properties. Abstract: Carboxylated cellulose nanocrystals (CNCs) were produced from cotton linter using a mixture of a dicarboxylic acid (maleic acid or succinic acid) and its corresponding anhydride with or without catalyst in acetic acid as solvent. The low solubilities of these dicarboxylic acids can ease chemical recovery and decrease environmental impact (especailly maleic acid is a U.S. FDA approved indirect food additive (21CFR175-177)) and capital costs compared with the conventional concentrated sulfuric acid hydrolysis for producing CNCs. The dicarboxylic-acid-produced CNCs (DC-CNCs) contained surface carboxyl groups of approximately 0.5 mmol/g, with ranges of dimensions of 50–150 nm in diameter and 50–700 nm in length. Birefringence was observed in the DC-CNC suspensions above critical concentrations. However, fingerprint texture was only observed in the DC-CNC suspensions produced with catalyst p -toluenesulfonic acid. Scanning electron microscopy images of the cross section of DC-CNC films revealed a periodic ordered multilayer structure. DC-CNCs were also produced using recycled dicarboxylic acids.